Inovasi dan Digitalisasi UMKM dalam Memanfaatkan Media Sosial untuk Membantu Pemasaran dan Promosi Kelompok Pandai Besi di Lembang Buntu Tangti - Adriana Madya Marampa; Helba Rundupadang (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Digitalization is very important for Micro, Small and Medium Enterprises (MSMEs). The aim of this MSME digitalization activity is to help MSMEs be able to market their products by helping to market and sell local blacksmith products in Lembang Buntu Tangti with the help of the Canva application. Apart from that, by taking advantage of technological advances in society, especially for MSME players. This activity is carried out in 8 stages: (1) Identifying needs, determining goals, (2) Explanation of the benefits of creating an Instagram account (3) Training on creating Instagram accounts (4) Training on creating Canva (5). Making Promotional Materials 6 Practices and Feedback (7) Monitoring and Evaluation (8) Documentation. The method used in implementing this community service program regarding digitalization of MSMEs is in the form of socialization and assistance to MSMEs. Based on the survey results, it is known that MSME players have started to utilize digital technology to develop their business so that they can adapt to the current pandemic conditions